Malignant mediastinal mesothelioma treated with anlotinib: a case report and review of the literature - Zhang, Yishi; He, Wan; Zhan, Ke; Zhang, Luobin; Cao, Hua; Xu, Ruilian (Frontiers in Oncology, 2023)
Malignant mesothelioma that originate from mediastinal (MMM) is a rare form of malignant pleural mesothelioma (MPM). The prognose of advanced stage MPM was poor and traditional treatment was chemotherapy. Here we present a patient with MMM that was treated with anlotinib, a multi-target multitargeted tyrosine kinase inhibitor (TKI) who had a 24 months-progression free survival (PFS). Further review of the literature showed that despite some explorations of applying small-molecule multitargeted TKIs in the treatment of MPM, but until today no large series had positive result. Anlotinib had been approved by the China Food and Drug Administration (CFDA) on treating non-small cell lung cancer, soft tissue sarcoma, renal cell carcinoma and medullary thyroid cancer. We assumed that the ability of anlotinib to target more tyrosine kinase receptors than most of other TKIs could contribute to the long duration of PFS in this case but further study is in need to further validate the efficacy of anlotinib in treatment of MPM.